Quantifying Nitrate Leaching under Commercial Red Raspberry Using Passive Capillary Wick Samplers. Issue 1 (14th February 2019) - Loo, Shawn E.; Zebarth, Bernie J.; Ryan, M. Cathryn; Forge, Thomas A.; Cey, Edwin E.
Abstract : Core Ideas: NO3 leaching was quantified by passive capillary wick samplers over 2 yr. NO3 leaching was three times greater in Year 1 than Year 2 (240 vs. 80 kg N ha −1 ). Increased Year 1 NO3 leaching reflected field renovation prior to monitoring period. There was strong seasonality in NO3 leaching from the field. Despite fertilizer banding in rows, 60% of NO3 leached from alleys between rows. Groundwater NO3 –N contamination in the Abbotsford‐Sumas Aquifer in British Columbia, Canada, has been attributed primarily to NO3 –N leaching from red raspberry ( Rubus idaeus L.); however, direct estimates of NO3 –N leaching are lacking. This study quantified the magnitude and timing of NO3 –N leaching under a commercial red raspberry field over 30 mo (October 2010–March 2013) using passive capillary wick samplers installed below the root zone at three row locations (irrigated row, nonirrigated row, and alley) after the critical period of field renovation and replanting. Substantial NO3 –N leaching (240 kg N ha −1 ) during the first year of monitoring was attributed to the effects of field renovation (including autumn chopping and incorporation of raspberry canes and soil fumigation and spring poultry broiler manure application) in the year prior to the initiation of monitoring. Lower NO3 –N leaching (80 kg N ha −1 ) occurred in the second year of monitoring under typical mineral fertilizer management practices. Strong seasonality of NO3 –N leaching was observed in both years, with ∼48% in autumn, 34% in spring and summer, and 17% in winter. Approximately 60% of the NO3 –N leaching was attributed to the alleys between raspberry rows, which did not receive mineral fertilizer or irrigation. The high proportion of leaching during spring and summer and from the alleys suggests that growing‐season irrigation practices and alley vegetation management, respectively, would be good targets for the development of improved practices. The samplers were effective in quantifying the magnitude and timing of NO3 –N leaching from a commercial agricultural field and informing the development of improved practices.